The influence of environmental enrichment with different kind of wood on some behavioural and fattening traits of rabbits housed in individual wire cages - Jordan, Dušanka (Acta agriculturae slovenica. Suplement, 2004)
The influence of addition of different types of wooden sticks as gnawing material for environmental enrichment on some behavioural and fattening traits was studied on 48 male New Zealand White rabbits of Slovenian male line SIKA. Animals were housed individually in wire cages equipped with feeder and nipple drinkers. Feed and water were available ad libitum, the duration of lighting was 12 hours. According to the type of wood placed in the cage, rabbits were equally allotted to four groups: control, oak, lime and Norway spruce. Rabbit behaviour was studied on 16 focus animals using continuous 24 hours video recording. Environmental enrichment had no significant influence on fattening traits and behaviour, except for eating, wood gnawing and frequency of caecotrophy. Rabbits in Norway spruce group ate significantly less time and less frequently and gnawed wood significantly longer and more often than rabbits in oak group.
Keywords: etologija; glodanje; kletke; kunci; les; obnašanje živali; okolje